Strengthening Religious Moderation through PTKIN and SIT Collaboration to Build Social Harmony - Kholil, Syukur; Ismail, Ismail; Dalimunthe, Maulana Andinata; Suhendar, Aris; Rambe, Rahmansyah Fadlul Al Karim (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This research aims to strengthen religious moderation through information-based education, which is conducted through collaboration between North Sumatra State Islamic University (UINSU) and Jabal Noor Integrated Islamic High School. This research was motivated by the low understanding of Jabal Noor Integrated Islamic High School students about the concept of religious moderation, which was previously only recorded at 40%. Using a qualitative approach and case study method, data was collected through interviews, observations, and documentation from principals, teachers, and students. The community service program in the form of counseling succeeded in increasing students' understanding of religious moderation, which after the implementation of the activity increased to 85%. The results showed that this collaboration succeeded in strengthening students' understanding of religious moderation and contributed to the formation of social harmony at school. Information-based education through counseling provides a better understanding of the importance of moderation in daily life, as well as how moderation values can be applied to support peaceful social life in the school environment. The implication of this research is the importance of strengthening collaboration between higher education institutions and schools in developing educational programs that promote religious moderation as a basic value in student character building, as well as encouraging a more inclusive atmosphere of social harmony in the community.